More means Worse – Asymmetric Information, Spatial Displacement and Sustainable Heritage Tourism - Silvia Caserta; Antonio Paolo Russo (Tinbergen Institute, 2001)
This paper analyses the market transformations in heritage tourism destinations when excessivetourism demand determines the emergence of a class of excursionists among visitors. Building onthe approach of Keane (1997) and Shapiro (1983), our model highlights some importantdimensions of sustainable tourism development. The lesser capacity of excursionists to learn thetrue quality of the tourist goods increases the convenience for producers to cut back on quality. Tocontinue to serve high quality goods and keep up the reputation of the destination as demandcontinues to grow, producers need to gain a mark-up on price that might not be sustained in acompetitive market. Hence the decline in “high-paying” demand segments which are increasinglysusbstituted by visitors with lesser quality expectations. In the end, the dynamics explained withthis approach are consistent with – and represent an economic reinterpretation of – the class ofevolutionary models known as “destination life cycle”, when they are applied to heritage cities.The regulator achieves a sustainable growth if it could enforce quality or information standards.However, the process should be managed at a spatial level that is rarely matched by formaladministrative competencies. Traditional tourism strategies are seldom successful when they try toprevent excessive growth by discouraging daily visits. This model helps to identify alternative andmore appropriate policy instruments.
Keywords: 330; Sustainable tourism; heritage tourism; excursionists; quality; reputation; Tourismus; Kultur; Lebenszyklus; Nachhaltige Entwicklung; Asymmetrische Information; Theorie